Histopathologic Differentiation between Enchondroma and Well-differentiated Chondrosarcoma: Evaluating the Efficacy of Diagnostic Histologic Structures - Shams Shariat Torbaghan; Mahdi Ashouri; Noushin Jalayer Naderi; Nima Baherini (Tabriz University of Medical Sciences, 2011)
Background and aims. Well-differentiated chondrosarcoma and enchondroma are similar in histopathologic aspects; therefore, special methods should be used to make a distinction between these benign and malignant tumors. The aim of this study was to evaluate the efficacy of a histopathologic method in the long-term follow-up for differentiating these lesions. Materials and methods. The medical records of patients with histopathologic diagnosis of chondrosarcoma and enchondroma were retrieved from the Institute of Cancer, Department of Pathology from 1981 to 2007 in this retrospective study. A total of 14 patients with chondrosarcoma and 7 patients with enchondroma were included. Tumor lobulation pattern and fibrous tissue around the lesions were used for histopathologic differentiation between well-differentiated chondrosarcoma and enchondroma. Method accuracy was evaluated by tumor recurrence in the long-term follow-up. Results. In the well-differentiated chondrosarcoma group, the follow-up period was 97 months. All the patients (100%) experienced recurrence. In the enchondroma group, the follow-up period was 129 months. There was no recurrence in this group. Conclusion. Lobulation pattern and fibrous tissue formation around the tumor can be an effective and helpful indicator for histopathologic differentiation between enchondroma and well-differentiated chondrosarcoma.